9-Aryl-phenalenones: Bioinspired thermally reversible photochromic compounds for photoswitching applications in the pico-to milliseconds range - Bresolí-Obach, Roger; Massad, Walter A.; Abudulimu, Abasi; Lüer, Larry; Flors, Cristina; Luis, Javier G.; Rosquete, Laura I.; Grillo, Teresa A.; Anamimoghadam, Ommid; Bucher, Götz; Nonell, Santi (Dyes and Pigments, 2020)
Ultrafast photochromic molecules are being actively investigated to meet the demand for fast optical switching systems. Inspired on the irreversible cyclization of 9-phenylphenalenone plant metabolites to yield highly-coloured naphthoxanthenes for the purpose of defense against pathogens, aryl-substituted phenalenones have been developed that undergo a similar but reversible photochromic reaction. The lifetime of the naphthoxanthene photoisomer spans nine orders of magnitude, ranging from tens of picoseconds to tens of milliseconds depending on the electronic properties of the 9-aryl group.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Chromene; Phenalenone; Photochromic; Photoswitch; β-phenyl quenching

Achieving High External Quantum Efficiency for ITIC-Based Organic Solar Cells with Negligible Homo Energy Offsets - Du, Huijun; An, Kang; Wang, Rong; Yin, Zhipeng; Peng, Feng; Lüer, Larry; Brabec, Christoph; Ying, Lei; Li, Ning (Advanced Energy Materials, 2024)
Minimizing energy loss in organic solar cells (OSCS) is critical for attaining high photovoltaic performance. Among the parameters that correlated to photovoltaic performance, the energy offsets between donor–acceptor pairs play a vital role in photoelectric conversion processes. For so far reported a large number of non-fullerene acceptors (NFAs), only Y6 and its derivatives can achieve external quantum efficiencies (EQEs) over 80% with negligible energy offsets when combined with polymeric donors. Thus, understanding the relationship between energy offsets and energy losses in representative NFAs is the key to further enhancing the efficiency of OSCs. In this study, a series of wide-bandgap polymer donors based on pyrrolo[3,4-f]benzotriazole-5,7(6H)-dione (TzBI) and benzo[1,2-c:4,5-c′] dithiophene-4,8-dione building blocks are combined with representative NFAs, including ITIC and Y6, to gain deep insights into their photovoltaic performances and related energy losses. Outstanding EQEs (≈70%) and suppressed non-radiative recombination are achieved at negligible energy offsets. Moreover, it is noted that a prolonged exciton lifetime of acceptor is not essential to obtain high EQEs in OSCs with negligible energy offsets. Eventually, ITIC derivatives with high electroluminescence efficiencies and near-infrared absorptions have the potential to be assembled to obtain high-efficiency OSCs.
CRIS-Team Scopus Importer:2024-02-16
Keywords: energy offsets; external quantum efficiency; non-fullerene acceptors; non-radiative energy loss

A digital twin to overcome long-time challenges in photovoltaics - Lüer, Larry; Peters, Ian Marius; Smith, Ana-Suncana; Dorschky, Eva; Eskofier, Björn; Liers-Bergmann, Frauke; Franke, Jörg; Sjarov, Martin; Brossog, Matthias; Guldi, Dirk Michael; Maier, Andreas; Brabec, Christoph (Joule, 2024)
The recent successes of emerging photovoltaics (PVs) are largely driven by innovations in material science. However, closing the gap to commercialization still requires significant progress to match contradicting requirements, such as performance, longevity, and recyclability. In this perspective, we envision the layout of a digital twin for PV materials able to provide the necessary acceleration of innovation. The layout combines machine learning approaches, as performed in materials acceleration platforms (MAPs), with physical models and digital twin concepts used in engineering. This layout will allow the use of high-throughput (HT) experimentation in MAPs to improve the parametrization of quantum chemical and solid-state models. In turn, the improved and generalized models can be used to obtain the crucial structural parameters. HT experimentation will thus yield a detailed understanding of generally valid structure-property relationships. We discuss the current state of the enabling technologies, namely fast scale-bridging surrogate models and large-scale optimization under uncertainty, and identify promising approaches for further development.<br
Keywords: digital twin; emerging photovoltaics; artificial intelligence; multi-scale simulations; optimization; high-throughput methods; materials acceleration platforms

Adjusting the energy of interfacial states in organic photovoltaics for maximum efficiency - Gasparini, Nicola; Camargo, Franco V.A.; Frühwald, Stefan; Nagahara, Tetsuhiko; Classen, Andrej; Roland, Steffen; Wadsworth, Andrew; Gregoriou, Vasilis G.; Chochos, Christos L.; Neher, Dieter; Salvador, Michael; Baran, Derya; et al. (Nature Communications, 2021)
A critical bottleneck for improving the performance of organic solar cells (OSC) is minimising non-radiative losses in the interfacial charge-transfer (CT) state via the formation of hybrid energetic states. This requires small energetic offsets often detrimental for high external quantum efficiency (EQE). Here, we obtain OSC with both non-radiative voltage losses (0.24 V) and photocurrent losses (EQE > 80%) simultaneously minimised. The interfacial CT states separate into free carriers with ≈40-ps time constant. We combine device and spectroscopic data to model the thermodynamics of charge separation and extraction, revealing that the relatively high performance of the devices arises from an optimal adjustment of the CT state energy, which determines how the available overall driving force is efficiently used to maximize both exciton splitting and charge separation. The model proposed is universal for donor:acceptor (D:A) with low driving forces and predicts which D:A will benefit from a morphology optimization for highly efficient OSC.
CRIS-Team Scopus Importer:2021-04-02

Aerial Photoluminescence Imaging of Photovoltaic Modules - Doll, Bernd; Wittmann, Ernst; Lüer, Larry; Hepp, Johannes; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Physica Status Solidi-Rapid Research Letters, 2023)
On-site imaging of modules in photovoltaic (PV) systems requires contact-free techniques with high throughput and low cost for commercial relevance. Photoluminescence imaging satisfies these requirements, but it has so far not been used for aerial imaging. Such a system faces unique engineering and operating challenges, including the need to mount a light source on the drone and identifying module defects from images taken under low- and nonuniform irradiance. Herein, in-house developed photoluminescence aerial imaging (PLAI) setup is presented and it is demonstrated that it can be used to identify defects even with a difference of excitation intensity of up to 50%. The setup consists of a hexacopter aerial drone equipped with an illumination unit and a near-infrared camera. The unit is capable of partially illuminating full-sized modules at night and capturing the photoluminescence response. In the maiden flight, a throughput of 13.6 PV modules per minute is achieved, and a throughput of 300 PV modules per minute is feasible. It is shown that the setup can be used to detect and identify cracks and potential induced degradation with high levels of confidence. These findings are verified by cross correlation and comparing captured photoluminescence images to electroluminescence images taken indoors.
CRIS-Team Scopus Importer:2023-05-26
Keywords: aerial inspection; photoluminescence; photovoltaic

Aerial photoluminescence imaging of PV modules - Doll, Bernd; Wittmann, Ernst; Lüer, Larry; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2023)
On-site imaging of photovoltaic systems requires methods that are high-throughput, low-cost and contact free for commercial relevance. Photoluminescence imaging satisfies these requirements, but it has so far not been used for aerial imaging due to a lack of a drone-mounted system. In this study, we present first results captured by our in-house developed PLAI (photoluminescence aerial imaging) setup. The setup consists of a hexacopter aerial drone equipped with an illumination unit and a near infrared camera. The unit is capable of partially illuminating full size modules at night and capturing the photoluminescence response. We show that the setup can be used to detect and identify defects such as cracks and potential-induced degradation with high levels of confidence.
CRIS-Team Scopus Importer:2024-12-16

A High Throughput Platform to Minimize Voltage and Fill Factor Losses - Haffner-Schirmer, Julian; Le Corre, Vincent Marc; Forberich, Karen; Egelhaaf, Hans-Joachim; Osterrieder, Tobias; Wortmann, Jonas; Liu, Chao; Weitz, Paul; Heumüller, Thomas; Bornschlegl, Andreas; Wachsmuth, Josua; Distler, Andreas; et al. (Advanced Energy Materials, 2025)
Organic photovoltaics (OPV) now can exceed 20% power conversion efficiency in single junction solar cells. To close the remaining gap to competing technologies, both fill factor and open-circuit voltage must be optimized. The Langevin reduction factor is a well-known concept that measures the degree to which charge extraction is favored over charge recombination. It is therefore ideally suited as an optimization target in high-throughput workflows; however, its evaluation so far requires expert interaction. Here, an integrated high-throughput workflow is presented, able to obtain the Langevin reduction factor within a few seconds with high accuracy without human intervention and thus suited for autonomous experiments. This is achieved by combining evidence from UV–vis spectra, current–voltage curves, and a novel implementation of microsecond transient absorption kinetics allowing, for the first time, the intrinsic determination of charge absorption cross-sections, which is crucial to reporting stationary charge densities. The method is demonstrated by varying the donor:acceptor ratio of the high performance OPV blend PM6:Y12. The high reproducibility of the method allows to find a strictly exponential relationship between the PM6 exciton energy and the Langevin reduction factor.
CRIS-Team Scopus Importer:2025-01-31
Keywords: charge dynamics; high throughput; Langevin reduction factor; organic photovoltaics; transient absorption kinetics

An Automated Workflow to Discover the Structure-Stability Relations for Radiation Hard Molecular Semiconductors - Bornschlegl, Andreas; Duchstein, Patrick; Wu, Jianchang; Rocha-Ortiz, Juan S.; Caicedo-Reina, Mauricio; Ortiz, Alejandro; Insuasty, Braulio; Zahn, Dirk; Lüer, Larry; Brabec, Christoph (Journal of the American Chemical Society, 2025)
Emerging photovoltaics for outer space applications are one of the many examples where radiation hard molecular semiconductors are essential. However, due to a lack of general design principles, their resilience against extra-terrestrial high-energy radiation can currently not be predicted. In this work, the discovery of radiation hard materials is accelerated by combining the strengths of high-throughput, lab automation and machine learning. This way, a large material library of more than 130 organic hole transport materials is automatically processed, degraded, and measured. The materials are degraded under ultraviolet-C (UVC) light in a nitrogen atmosphere, serving as the conditions for electromagnetic radiation hardness tests. A value closely related to the differential quantum yield for photodegradation is extracted from the evolution of the UV-visible (UV-vis) spectra over time and used as a stability target. Following this procedure, a stability ranking spanning over 3 orders of magnitude was obtained. Combining Gaussian Process Regression based on predictors from structural fingerprints and manual filtering of the materials by features, structure-stability relations for UVC stable materials could be found: Fused aromatic ring clusters are beneficial, whereas thiophene, methoxy and vinylene groups are detrimental. Comparing the UV-vis spectra of the degraded material in film and solution, bond cleavage could be made out as the leading degradation mechanism. Even though UVC light can in principle break most organic bonds, the stable materials are able to distribute and dissipate the energy well enough so that the chemical structures remain stable. The established predictive model quantifies the effect of specific molecular features on UVC stability, allowing chemists to consider UVC stability in their molecular design strategy. In the future, a larger data set will allow to inversely design molecular semiconductors which show high performance and radiation hardness at the same time.
CRIS-Team Scopus Importer:2025-01-31

Autonomous Optimization of Air-Processed Perovskite Solar Cell in a Multidimensional Parameter Space - Zhang, Jiyun; Le Corre, Vincent M.; Wu, Jianchang; Du, Tian; Osterrieder, Tobias; Zhang, Kaicheng; Zhang, Handan; Lüer, Larry; Hauch, Jens; Brabec, Christoph J. (Advanced Energy Materials, 2025)
Traditional optimization methods often face challenges in exploring complex process parameter spaces, which typically result in suboptimal local maxima. Here an autonomous framework driven by a machine learning (ML)-guided automated platform is introduced to optimize the fabrication conditions of additive- and passivation-free perovskite solar cells (PSCs) under ambient conditions. By effectively exploring a 6D parameter space, this method identifies five parameter sets achieving efficiencies above 23%, with a peak efficiency of 23.7% with limited experimental budgets. Feature importance analysis indicates that the rotation speeds during the first and second steps of perovskite processing are the most influential factors affecting device performance, thereby meriting prioritization in the optimization efforts. These results demonstrate the exceptional capability of the autonomous framework in addressing complex process parameter optimization challenges and its potential to advance perovskite photovoltaic technology. Beyond PSCs, this work provides a reliable and comprehensive strategy for optimizing solution-processed semiconductors and highlights the broader applications of autonomous methodologies in materials science.
CRIS-Team Scopus Importer:2025-01-31
Keywords: air-processing perovskite solar cells; automation framework; autonomous optimization; device acceleration platform; machine learning

Binary cations minimize energy loss in the wide-band-gap perovskite toward efficient all-perovskite tandem solar cells - Zhang, Kaicheng; Liu, Chao; Peng, Zijian; Li, Chaohui; Tian, Jingjing; Li, Canru; García Cerrillo, José; Dong, Lirong; Streller, Fabian; Späth, Andreas; Musiienko, Artem; Englhard, Jonas; et al. (Joule, 2024)
Perovskite-based tandem solar cells stand at the forefront of photovoltaic innovation due to their exceptional performance and cost-effective fabrication. This study focuses on minimizing energy losses within a 1.80 eV perovskite sub-cell. We demonstrate that the surface treatment of perovskite with binary guanidinium bromide and 4-fluorophenylammonium iodide synergistically reduces defect densities and adjusts interfacial energy-level alignment. The enhanced passivation effect and the formation of a surface dipole significantly reduce nonradiative recombination and transport losses, leading to a notable increase in the open-circuit voltage and fill factor product, thereby achieving an impressive power conversion efficiency (PCE) of 19.0%. The reproducibility of these findings is confirmed by consistent results across different laboratories. Furthermore, integration with a narrow-band-gap perovskite yields an all-perovskite tandem device with a PCE of 27.2%. This comprehensive understanding of the pivotal role of spacer cations in surface treatment significantly advances the pathway toward efficient perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-08-30
Keywords: 2D phases; all-perovskite tandem solar cell; energy loss; energy-level alignment; nonradiative recombination; passivation; spacer cations; surface dipole; surface treatment; wide band-gap perovskite

Bridging theory and experiment in defect-tolerant semiconductors for photovoltaics - Hammer, Maria; Schlott, Hannah; Lüer, Larry; Brabec, Christoph; Sytnyk, Mykhailo; Will, Johannes; Meyer, Bernd; Heiß, Wolfgang (Nature Reviews Materials, 2025)
Defect tolerance is a concept applied in photovoltaics to explain semiconductors such as lead-halide perovskites that excel without relying on single-crystalline growth. It differentiates from the mere absence of defects, emphasizing on minimizing the influence of defects on minority carrier lifetimes. Whether defect tolerance is the only reason for the superiority of lead-halide-perovskite-based solution-processed solar cells is still controversial. However, the defect tolerance of various semiconductor structures and materials has been experimentally suggested and, in some cases, proven. In this Perspective, we explore defect tolerance across material science, defect characterization and computational modelling. With a primary focus on electrically or optically active defects, we systematically compare computational and experimental results from the literature. We aim to address the complexity arising from diverse theoretical approaches that have yielded partially contradictory results. Additionally, experimental findings have been subject to varied interpretations, ranging from defect signals to ion migration. We endeavour to chart a course through this intricacy and seek to establish a rigorous framework for the identification and quantitative assessment of defect toleranc

Building process design rules for microstructure control in wide-bandgap mixed halide perovskite solar cells by a high-throughput approach - Akhundova, Fatima; Lüer, Larry; Osvet, Andres; Hauch, Jens; Peters, Ian Marius; Forberich, Karen; Li, Ning; Brabec, Christoph (Applied Physics Letters, 2021)
Wide bandgap mixed halide perovskites ABX3, in which X can be I, Br, or Cl, are promising materials to form highly efficient optoelectronic devices, because the optical bandgap can be controlled over a wide range by variation of the halogen composition. However, significant nonradiative losses must be overcome to approach the efficiency limit of single-junction solar cells. Here, we present a high throughput-based investigation of the influence of processing parameters on nonradiative losses in the perovskite bulk. We perform antisolvent crystallization during spin coating and vary the solvent type, its volume, and the temperature of the subsequent annealing step. We use the photoluminescence quantum yield (PLQY) as a proxy to the presence of nonradiative losses and PL spectra as a qualitative probe for sample morphology. Using Gaussian process regression, we find that we can reliably predict PLQY from the PL spectral shape. This means that the PL spectral shape conveys the essential photophysics controlling PL quenching and thus nonradiative charge recombination. In comparison with scanning electron micrographs and x-ray diffraction data, we find that nonradiative losses in polycrystalline perovskite films are caused by increased domain size dispersion. Our method provides a simple and fast structure-sensitive in-line probe for fast morphology optimization in a high-throughput fashion.
CRIS-Team Scopus Importer:2021-06-25

Bypassing the Single Junction Limit with Advanced Photovoltaic Architectures - Lüer, Larry; Peters, Ian Marius; Le Corre, Vincent Marc; Forberich, Karen; Guldi, Dirk Michael; Brabec, Christoph (Advanced Materials, 2023)
Multijunction devices and photon up- and down-conversion are prominent concepts aimed at increasing photovoltaic efficiencies beyond the single junction limit. Integrating these concepts into advanced architectures may address long-standing issues such as processing complexity, microstructure control, and resilience against spectral changes of the incoming radiation. However, so far, no models have been established to predict the performance of such integrated architectures. Here, a simulation environment based on Bayesian optimization is presented, that can predict and virtually optimize the electrical performance of multi-junction architectures, both vertical and lateral, in combination with up- and down-conversion materials. Microstructure effects on performance are explicitly considered using machine-learned predictive models from high throughput experimentation on simpler architectures. Two architectures that would surpass the single junction limit of photovoltaic energy conversion at reasonable complexity are identified: a vertical “staggered half octave system,” where selective absorption allows the use of 6 different bandgaps, and the lateral “overlapping rainbow system” where selective irradiation allows the use of a narrowband energy acceptor with reduced voltage losses, according to the energy gap law. Both architectures would be highly resilient against spectral changes, in contrast with two terminal multi-junction architectures which are limited by Kirchhoff's law.<br

Controlling Intermediate Phase Formation to Enhance Photovoltaic Performance of Inverted FA-Based Perovskite Solar Cells - Li, Chaohui; Park, Hyoungwon; Qiu, Shudi; Streller, Fabian; Zhang, Kaicheng; Peng, Zijian; Byun, Jiwon; Tian, Jingjing; Maiti, Santanu; Xie, Zhiqiang; Dong, Lirong; Liu, Chao; et al. (ACS Energy Letters, 2024)
Formamidinium (FA)-based perovskites exhibit significant potential for highly efficient photovoltaics due to their promising optoelectronic properties and optimal bandgap. However, the undesired inactive phase arises from multiple crystal nucleation pathways formed by various intermediate phases during the film formation process, persistently accompanying it. FA-based perovskites frequently struggle to form uniform, highly crystalline films. This challenge complicates the development of reliable and highly reproducible crystallization processes for perovskites and the establishment of guidelines for controlling the α-phase formation. In this work, we investigate the role of poly(acrylonitril-co-methyl acrylate) (PAM) to simultaneously control nucleation and subsequent α-phase crystallization. This successfully demonstrates the regulation of oriented crystal growth through the creation of a PAM-PbI2 intermediate. Ultimately, PAM-modified p-i-n architecture devices obtain a promising power conversion efficiency (PCE) of 25.30%, with VOC (1.211 V), achieving 95% of the detailed balance limit. Additionally, PAM-modified devices maintain ≥90% of the initial efficiency for 1000 h under 1 sun and 65 °C operation.
CRIS-Team Scopus Importer:2024-11-22

Correction to: Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime (Nature Communications, (2024), 15, 1, (2002), 10.1038/s41467-024-46145-7) - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
Correction to: Nature Communicationshttps://doi.org/10.1038/s41467-024-46145-7, published online 05 March 2024 In this article, Junsheng Luo and Bowen Liu should have been denoted as equally contributing authors. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17

Cutting “lab-to-fab” short: high throughput optimization and process assessment in roll-to-roll slot die coating of printed photovoltaics - Wagner, Michael; Distler, Andreas; Le Corre, Vincent Marc; Zapf, Simon; Baydar, Burak; Schmidt, Hans-Dieter; Heyder, Madeleine; Forberich, Karen; Lüer, Larry; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy and Environmental Science, 2023)
Commercialization of printed photovoltaics requires knowledge of the optimal composition and microstructure of the single layers, and the ability to control these properties over large areas under industrial conditions. While microstructure optimization can be readily achieved by lab scale methods, the transfer from laboratory scale to a pilot production line (“lab to fab”) is a slow and cumbersome process: first, the difficulty of operating structure-sensitive methods in-line impedes proper microstructure characterization, and second, the processing-functionality relationship must be redetermined for every material combination as the results obtained by typical lab-scale spin-coating cannot be directly transferred to other coating methods. Here, we show how we can optimize the performance of organic solar cells and at the same time assess process performance in a 2D combinatorial approach directly on an industrially relevant slot die coating line. This is enabled by a multi-nozzle slot die coating head allowing parameter variations along and across the web. This modification allows us to generate and analyze 3750 devices in a single coating run, varying the active layer donor : acceptor ratio and the thickness of the electron transport layer (ETL). We use Gaussian Process Regression (GPR) to exploit the whole dataset for precise determination of the optimal parameter combination. Performance-relevant features of the active layer morphology are inferred from UV-Vis absorption spectra. By mapping morphology in this way, small undesired gradients of process conditions (extrusion rates, annealing temperatures) are detected and their effect on device performance is quantified. The correlation between process parameters, morphology and performance obtained by GPR provides hints to the underlying physics, which are finally quantified by automated high-throughput drift-diffusion simulations. This leads to the conclusion that voltage losses which are observed for very thin ETL coatings are due to incomplete coverage of the electrode by the ETL, which causes enhanced surface recombination.
CRIS-Team Scopus Importer:2023-11-10

Dynamics of backsheet-driven insulation issues - Buerhop-Lutz, Claudia; Lüer, Larry; Stroyuk, Oleksandr; Hauch, Jens; Peters, Ian Marius (Solar Energy Materials and Solar Cells, 2023)
To reap in the full benefit of high-efficiency solar cells and modules, the quality of the polymer encapsulant and backsheet (BS) materials is essential. Recent field studies show that early degrading backsheets cause safety issues and inverter shutdowns, resulting in yield losses. The dynamic development of degradation is important but is rarely studied because of the lack of proper datasets with meaningful and sufficient data. We studied inverter data of solar panels with a combined capacity of about 1 MWp for more than nine years including ground impedance (GI), and we labelled BS-types using our in-house identification method. Every inverter was connected to modules with exclusively a single BS-type, namely three-multilayer BSs denoted by their outer air layer: PA (polyamide), FC (fluorinated coating), and PVDF (polyvinylidene fluoride). We present, for the first time, an analysis of the degradation dynamics of GI, using a trained Gaussian Process Regression model. Using this model, we derived key degradation parameters, namely GI loss rates and time points for the onset of degradation. We found that PVDF BSs are associated with very low GI loss rates, while loss rates for PA are threefold higher with an onset at 6.6 year of operation for PA. FC BS-related loss rates were humidity dependent and two times higher those of PA; the onset was determined at 4.9 year of operation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Backsheet; Degradation rate; Gaussian Process Regression; Insulation resistance; Machine learning

Elucidating How Low Energy Offset Matters to Performance of Nonfullerene Acceptor-Based Solar Cells - Tokmoldin, Nurlan; Sun, Bowen; Moruzzi, Floriana; Patterson, Acacia; Alqahtani, Obaid; Wang, Rong; Collins, Brian A.; McCulloch, Iain; Lüer, Larry; Brabec, Christoph; Neher, Dieter; Shoaee, Safa (ACS Energy Letters, 2023)
The energetic offset between the highest occupied molecular orbitals of the donor and acceptor components of organic photovoltaic blends is well-known to affect the device efficiency. It is well-established that a decreasing offset increases the open-circuit voltage but reduces the short-circuit current, which has been explained by insufficient exciton dissociation. However, the impact of the offset on the fill factor and underlying processes is less clear. Here, we study free charge generation and recombination in three different nonfullerene acceptors, Y6, ITIC, and o-IDBTR, blended with the same donor polymer PM6. We demonstrate that a diminishing offset results in field-dependent charge generation related to field-assisted exciton dissociation. On the other hand, reformation of excitons from free charges is identified as an additional channel for charge recombination, which goes along with a substantial rise in the bimolecular recombination coefficient. In combination of these two effects, the fill factor drops considerably with a decreasing energy offset. Using the comparison between PM6:ITIC and PM6:o-IDBTR, we show that bulk properties such as morphology and carrier mobilities can not fully explain the observed difference in performance, highlighting the importance of interfacial kinetics and thermodynamics in controlling the device efficiency, both through generation and recombination of charge carriers.
CRIS-Team Scopus Importer:2023-07-14

Elucidating the Full Potential of OPV Materials Utilizing a High-Throughput Robot-Based Platform and Machine Learning - Du, Xiaoyan; Lüer, Larry; Heumüller, Thomas; Wagner, Jerrit; Berger, Christian; Osterrieder, Tobias; Wortmann, Jonas; Langner, Stefan; Vongsaysy, Uyxing; Bertrand, Melanie; Li, Ning; Stubhan, Tobias; et al. (Joule, 2021)
Evaluating the potential of organic photovoltaic (OPV) materials and devices for industrial production is a multidimensional optimization process with an incredibly large parameter space. Here, we demonstrate automated OPV material and device characterization in terms of efficiency and photostability. Gaussian process regression (GPR) prediction based on optical absorption features guided the optimization process with promising prediction accuracy for PV parameters and burn-in losses. With ∼100 process conditions, screening for efficiency and photostability can be finished within 70 h. The highest power conversion efficiency (PCE) of 14% was achieved by fully automated device fabrication in air with a model material system PM6:Y6. Improving molecular ordering has been identified as the most promising motif for further efficiency optimization. Thin active layers combined with medium thermal annealing temperature are favorable to simultaneously improve efficiency and suppress burn-in losses. The platform and protocol may be expanded to any solution-processed organic semiconductor and interface materials.
CRIS-Team Scopus Importer:2021-02-05
Keywords: automation; efficiency; high-throughput methods; machine learning; organic photovoltaics; photostability; processing optimization

Enhancing Planar Inverted Perovskite Solar Cells with Innovative Dumbbell-Shaped HTMs: A Study of Hexabenzocoronene and Pyrene-BODIPY-Triarylamine Derivatives - Rocha-Ortiz, Juan S.; Wu, Jianchang; Wenzel, Jonas; Bornschlegl, Andreas; Perea, Jose Dario; Leon, Salvador; Barabash, Anastasia; Wollny, Anna-Sophie; Guldi, Dirk Michael; Zhang, Jiyun; Insuasty, Alberto; Lüer, Larry; et al. (Advanced Functional Materials, 2023)
Keywords: hexabenzocoronene; donor–acceptor; BODIPY; π-conjugation; perovskite solar cells; hole-transport materials

Highly Efficient Bilayer Polymer Solar Cells Using the Method of Sequential Processing with Additive Bilayer - Lee, Jihoon; Jang, Soyeong; Tamilavan, Vellaiappillai; Li, Ning; Wang, Rong; Lüer, Larry; Lee, Dalyong; Yoon, Jung Won; Lee, Bo Ram; Choi, Hyosung; Park, Sung Heum; Brabec, Christoph (Solar RRL, 2023)
Despite the research value of bilayer organic solar cells (OSCs) for commercialization in the future, the bulk-heterojunction (BHJ) structure dominates the fabrication of OSCs because of its higher power conversion efficiency (PCE) compared with bilayer OSCs. Herein, four different types of bilayer OSC structures using sequential processing (SP) with an additive bilayer are investigated and considerably enhanced device performance is demonstrated. The performance of our bilayer devices based on a wide bandgap (PBDT-DPPD-TPD; P2) polymer and [6,6]-phenyl C61-butyric acid methyl ester (PCBM) is improved from 2.88% for the conventional bilayer structure to 6.62%. More importantly, remarkable PCEs of 8.78% and 15.16% for PTB7-Th/PCBM and PM6/Y6 bilayer OSCs, respectively, using the SP with additive bilayer method are achieved and the inhomogeneity issues of the BHJ structure are successfully addressed. Herein, a novel way to overcome the low efficiency of bilayer OSCs is suggested and an unprecedented possibility of renovation, breaking the standardization of OSC research, is presented.
CRIS-Team Scopus Importer:2023-01-20
Keywords: bilayer structures; high efficiency; organic solar modules; polymer solar cells; processing additives

Highly Efficient Photocatalytic Hydrogen Evolution Using a Self-Assembled Octupolar Molecular System - Lee, Hyun-Jun; Abudulimu, Abasi; Carlos Roldao, Juan; Nam, Hyunwoo; Gierschner, Johannes; Lüer, Larry; Park, Soo Young (Chemphotochem, 2022)
A highly efficient photocatalytic hydrogen evolution system was prepared by using an octupolar molecule as a building block of self-assembled nanoparticles. The photocatalytic system showed an enhanced hydrogen evolution reaction (HER) rate upon the addition of halide ions, which was attributed to an external heavy atom effect enhancing intersystem crossing. The HER rate of the photocatalytic system was proportional to the atomic weight and concentration of halide ion additives, and its maximum HER rate reached 460 mmol/g ⋅ h in the presence of iodide ions and a metal co-catalyst. Further, the photocatalytic system without any halide ion additives generated hydrogen gas utilizing seawater and stimulated sunlight with remarkable efficiency (apparent quantum yield∼3.8 %).
CRIS-Team Scopus Importer:2022-10-21
Keywords: hydrogen evolution; intersystem crossing; photocatalysis; self-assembly; water splitting

Impact of 2D Ligands on Lattice Strain and Energy Losses in Narrow-Bandgap Lead–Tin Perovskite Solar Cells - Zhang, Kaicheng; Vincze, Andrej; Metwalli, Ezzeldin; Zhang, Jiyun; Liu, Chao; Meng, Wei; Zhang, Boxue; Tian, Jingjing; Heumüller, Thomas; Xie, Zhiqiang; Luo, Junsheng; Osvet, Andres; et al. (Advanced Functional Materials, 2023)
Mixed lead and tin (Pb/Sn) hybrid perovskites exhibit a great potential in fabricating all-perovskite tandem devices due to their easily tunable bandgaps. However, the energy deficit and instability in Pb/Sn perovskite solar cells (PSCs) constrain their practical applications, which renders defect passivation engineering indispensable to develop highly efficient and long-term stable PSCs. Herein, the mechanisms of strain tailoring and defect passivation in Pb/Sn PSCs by 2D ligands are investigated. The 2D ligands include electroneutral cations with long alkyl chain (LAC), iodates with relatively short alkyl chain (SAC) and their mixtures. This study reveals that LAC ligands facilitate the relaxation of tensile strain in perovskite films while SAC ligands cause strain buildup. By mixing LAC/SAC ligands, tensile strain in perovskite films can be balanced which improves solar cell performance. PSCs with admixed β-guanidinopropionic acid (GUA)/phenethylammonium iodide (PEAI) exhibit enhanced open circuit voltage and fill factor, which is attributed to reduced nonradiative recombination losses in the bulk and at the interfaces. Furthermore, the operational stability of PSCs is slightly improved by the mixed 2D ligands. This work reveals the mechanisms of 2D ligands in strain tailoring and defect passivation toward efficient and stable narrow-bandgap PSCs.
CRIS-Team Scopus Importer:2023-07-07
Keywords: 2D ligand passivation; energy losses; lead/tin perovskite solar cells; stability; strain tailoring

In Situ Probing the Crystallization Kinetics in Gas-Quenching-Assisted Coating of Perovskite Films - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Jang, Dongju; Le Corre, Vincent Marc; García Cerrillo, José; Ronsin, Olivier J.J.; Yang, Fu; Guo, Fei; Zhang, Kaicheng; Lüer, Larry; Harting, Jens; et al. (Advanced Energy Materials, 2024)
The pursuit of commercializing perovskite photovoltaics is driving the development of various scalable perovskite crystallization techniques. Among them, gas quenching is a promising crystallization approach for high-throughput deposition of perovskite films. However, the perovskite films prepared by gas-quenching assisted blade coating are susceptible to the formation of pinholes and frequently show inferior crystallinity if the interplay between film coating, film drying, and crystallization kinetics is not fully optimized. That arguably requires a thorough understanding of how single processing steps influence the crystallization kinetics of printed perovskite films. Here, in situ optical spectroscopies are integrated into a doctor-blading setup that allows to real-time monitor film formation during the gas-quenching process. It is found that the essential role of gas quenching treatment is in achieving a smooth and compact perovskite film by controlling the nucleation rate. Moreover, with the assistance of phase-field simulations, the role of excessive methylammonium iodide is revealed to increase grain size by accelerating the crystal growth rate. These results show a tailored control of crystal growth rate is critical to achieving optimal film quality, leading to fully printed solar cells with a champion power conversion efficiency of 19.50% and mini solar modules with 15.28% efficiency are achieved.
CRIS-Team Scopus Importer:2024-01-12
Keywords: blade coating; fully printed perovskite photovoltaics; gas quenching; in situ techniques; phase-field simulations

Intercalating-Organic-Cation-Induced Stability Bowing in Quasi-2D Metal-Halide Perovskites - Zhang, Jiyun; Langner, Stefan; Wu, Jianchang; Kupfer, Christian; Lüer, Larry; Meng, Wei; Zhao, Baolin; Liu, Chao; Daum, Manuel; Osvet, Andres; Li, Ning; Halik, Marcus; et al. (ACS Energy Letters, 2022)
Quasi-2D metal-halide perovskites with Ruddlesden-Popper structures have shown promising stability due to the protective effects of the intercalating organic cations. However, a systematic study of the effect of intercalating organic cations on stability has rarely been reported. Here we use a high-throughput-robot platform to fabricate over 300 perovskite films and study the effect of cations and their concentrations on the thermal stability of perovskite films. We find that approximately 20-25 mol % of intercalating organic cations into MAPbI3 (nominal n = 4/5) can maximize the film stability, while higher/lower concentrations lead to inferior stability, which is termed stability bowing in analogy to band-gap bowing. A model with two competitive effects of the intercalating organic cation (better protection vs more defects) is proposed to rationalize this behavior. We anticipate this work to provide new insights into the stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-02-11

Inverse design workflow discovers hole-transport materials tailored for perovskite solar cells - Wu, Jianchang; Torresi, Luca; Hu, Manman; Reiser, Patrick; Zhang, Jiyun; Rocha-Ortiz, Juan S.; Wang, Luyao; Xie, Zhiqiang; Zhang, Kaicheng; Park, Byung-Wook; Barabash, Anastasia; Zhao, Yicheng; et al. (Science, 2024)
The inverse design of tailored organic molecules for specific optoelectronic devices of high complexity holds an enormous potential but has not yet been realized. Current models rely on large data sets that generally do not exist for specialized research fields. We demonstrate a closed-loop workflow that combines high-throughput synthesis of organic semiconductors to create large datasets and Bayesian optimization to discover new hole-transporting materials with tailored properties for solar cell applications. The predictive models were based on molecular descriptors that allowed us to link the structure of these materials to their performance. A series of high-performance molecules were identified from minimal suggestions and achieved up to 26.2% (certified 25.9%) power conversion efficiency in perovskite solar cell
CRIS-Team Scopus Importer:2025-02-04

Maximizing Performance and Stability of Organic Solar Cells at Low Driving Force for Charge Separation - Lüer, Larry; Wang, Rong; Liu, Chao; Dube, Henry; Heumüller, Thomas; Hauch, Jens; Brabec, Christoph (Advanced Science, 2023)
Thanks to the development of novel electron acceptor materials, the power conversion efficiencies (PCE) of organic photovoltaic (OPV) devices are now approaching 20%. Further improvement of PCE is complicated by the need for a driving force to split strongly bound excitons into free charges, causing voltage losses. This review discusses recent approaches to finding efficient OPV systems with minimal driving force, combining near unity quantum efficiency (maximum short circuit currents) with optimal energy efficiency (maximum open circuit voltages). The authors discuss apparently contradicting results on the amount of exciton binding in recent literature, and approaches to harmonize the findings. A comprehensive view is then presented on motifs providing a driving force for charge separation, namely hybridization at the donor:acceptor interface and polarization effects in the bulk, of which quadrupole moments (electrostatics) play a leading role. Apart from controlling the energies of the involved states, these motifs also control the dynamics of recombination processes, which are essential to avoid voltage and fill factor losses. Importantly, all motifs are shown to depend on both molecular structure and process conditions. The resulting high dimensional search space advocates for high throughput (HT) workflows. The final part of the review presents recent HT studies finding consolidated structure–property relationships in OPV films and devices from various deposition methods, from research to industrial upscaling.
CRIS-Team Scopus Importer:2023-12-15
Keywords: electrostatics; exciton binding energy; high throughput methods; hybridization; open circuit voltage losses; organic photovoltaics

Observation of reversible light degradation in organic photovoltaics induced by long-persistent radicals - Zhang, Difei; Liu, Chao; Zhang, Kaicheng; Jia, Yanhua; Zhong, Wenkai; Qiu, Weidong; Li, Yuanfeng; Heumüller, Thomas; Forberich, Karen; Le Corre, Vincent Marc; Lüer, Larry; Li, Ning; et al. (Energy and Environmental Science, 2023)
With the rapid development of organic photovoltaics, device stability has become a crucial obstacle hindering their transition from laboratory-scale to industrial applications. However, it still remains unclear how light differs from heat in driving trap formation and device degradation. On the basis of the PTzBI-dF:Y6-BO system, it is observed that the post-thermal annealing on these high-performance organic solar cells can partially recover the light-induced burn-in losses. The recovery process is found to be correlated with a reversible charge extraction ability, reversible trap density of state, local charge carrier density and charge accumulation. Herein, we propose an innovative mechanism for light degradation in organic photovoltaic devices, which is triggered by the presence of light-induced long-persistent radicals. The findings offer deep insights into light degradation of organic photovoltaics and a new perspective for improving device stability under long-term operation.
CRIS-Team Scopus Importer:2023-12-01

On the critical competition between singlet exciton decay and free charge generation in non-fullerene based organic solar cells with low energetic offsets - Pranav, Manasi; Shukla, Atul; Moser, David; Rumeney, Julia; Liu, Wenlan; Wang, Rong; Sun, Bowen; Smeets, Sander; Tokmoldin, Nurlan; Cao, Yonglin; He, Guorui; Beitz, Thorben; et al. (Energy and Environmental Science, 2024)
Reducing voltage losses while maintaining high photocurrents is the holy grail of current research on non-fullerene acceptor (NFA) based organic solar cell. Recent focus lies in understanding the various fundamental mechanisms in organic blends with minimal energy offsets - particularly the relationship between ionization energy offset (ΔIE) and free charge generation. Here, we quantitatively probe this relationship in multiple NFA-based blends by mixing Y-series NFAs with PM6 of different molecular weights, covering a broad power conversion efficiency (PCE) range: from 15% down to 1%. Spectroelectrochemistry reveals that a ΔIE of more than 0.3 eV is necessary for efficient photocurrent generation. Bias-dependent time-delayed collection experiments reveal a very pronounced field-dependence of free charge generation for small ΔIE blends, which is mirrored by a strong and simultaneous field-dependence of the quantified photoluminescence from the NFA local singlet exciton (LE). We find that the decay of singlet excitons is the primary competition to free charge generation in low-offset NFA-based organic solar cells, with neither noticeable losses from charge-transfer (CT) decay nor evidence for LE-CT hybridization. In agreement with this conclusion, transient absorption spectroscopy consistently reveals that a smaller ΔIE slows the NFA exciton dissociation into free charges, albeit restorable by an electric field. Our experimental data align with Marcus theory calculations, supported by density functional theory simulations, for zero-field free charge generation and exciton decay efficiencies. We conclude that efficient photocurrent generation generally requires that the CT state is located below the LE, but that this restriction is lifted in systems with a small reorganization energy for charge transfer.
CRIS-Team Scopus Importer:2024-10-04

Organic solar cells using oligomer acceptors for improved stability and efficiency - Liang, Youcai; Zhang, Difei; Wu, Zerun; Jia, Tao; Lüer, Larry; Tang, Haoran; Hong, Ling; Zhang, Jiabin; Zhang, Kai; Brabec, Christoph; Li, Ning; Huang, Fei (Nature Energy, 2022)
The power conversion efficiencies of organic solar cells (OSCs) have reached over 19%. However, the combination of high efficiency and long-term stability is still a major conundrum of commercialization. Here a Y6-analogue and a 2,2′-bithiophene unit are utilized to construct a series of oligomer acceptors to investigate the effect of molecular size and packing properties on photovoltaic performance. By altering the molecular chain length, we modify the thermal properties, crystallization behaviours and molecular packing and achieve an optimal microstructure and a more stable morphology in blend films. A combination of efficiencies over 15% and an extrapolated T80 lifetime over 25,000 h, which equates to an average lifetime exceeding 16 years in Guangzhou, is achieved for binary OSCs based on an oligomer acceptor. This work emphasizes the importance of oligomeric strategy in tuning molecular packing behaviours and blend morphology, leading to development of novel non-fullerene acceptors for stable and efficient OSCs.
CRIS-Team Scopus Importer:2022-11-25

Overcoming efficiency and cost barriers for large-area quantum dot photovoltaics through stable ink engineering - Shi, Guozheng; Ding, Xiaobo; Liu, Zeke; Liu, Yang; Chen, Yifan; Liu, Cheng; Ni, Zitao; Wang, Haibin; Ito, Katsuji; Igarashi, Keisuke; Feng, Kun; Zhang, Kaicheng; et al. (Nature Energy, 2025)
The bottom-up construction of electronics from colloidal quantum dots (CQDs) could innovate nanotechnology manufacturing through printing. However, the unstable and expensive semiconductive CQD inks make the scaling up of CQD electronics challenging. Here we develop a strategy for engineering the solution chemistry of lead sulfide (PbS) CQD inks prepared from a low-cost direct synthesis method. By creating an iodine-rich environment in weakly coordinating solvents, we convert the iodoplumbates into functional anions, which condense into a robust surface shell. The fully charged electrostatic surface layer prevents aggregation and epitaxial fusion of CQDs, yielding stable inks. By eliminating the fusion-induced inter-band states, we print a compact CQD film with uniformity in three dimensions, flattened energy landscape and improved carrier transport. We achieved a certified efficiency of 13.40% on 0.04 cm2 cells, with a 300-fold increase in active area, scaling up to a 12.60 cm2 module with a certified efficiency of 10%.
CRIS-Team Scopus Importer:2025-04-18

Overcoming optical losses in thin metal-based recombination layers for efficient n-i-p perovskite-organic tandem solar cells - Tian, Jingjing; Liu, Chao; Forberich, Karen; Barabash, Anastasia; Xie, Zhiqiang; Qiu, Shudi; Byun, Jiwon; Peng, Zijian; Zhang, Kaicheng; Du, Tian; Sathasivam, Sanjayan; Macdonald, Thomas J.; et al. (Nature Communications, 2025)
Perovskite-organic tandem solar cells (P-O-TSCs) hold substantial potential to surpass the theoretical efficiency limits of single-junction solar cells. However, their performance is hampered by non-ideal interconnection layers (ICLs). Especially in n-i-p configurations, the incorporation of metal nanoparticles negatively introduces serious parasitic absorption, which alleviates photon utilization in organic rear cell and decisively constrains the maximum photocurrent matching with front cell. Here, we demonstrate an efficient strategy to mitigate optical losses in Au-embedded ICLs by tailoring the shape and size distribution of Au nanoparticles via manipulating the underlying surface property. Achieving fewer, smaller, and more uniformly spherical Au nanoparticles significantly minimizes localized surface plasmon resonance absorption, while maintaining efficient electron-hole recombination within ICLs. Consequently, optimized P-O-TSCs combining CsPbI2Br with various organic cells benefit from a substantial current gain of >1.5 mA/cm2 in organic rear cells, achieving a champion efficiency of 25.34%. Meanwhile, optimized ICLs contribute to improved long-term device stability.
CRIS-Team Scopus Importer:2025-01-31

Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
The development of a robust quasi-ohmic contact with minimal resistance, good stability and cost-effectiveness is crucial for perovskite solar cells. We introduce a generic approach featuring a Lewis-acid layer sandwiched between dopant-free semicrystalline polymer and metal electrode in perovskite solar cells, resulting in an ideal quasi-ohmic contact even at elevated temperature up to 85 °C. The solubility of Lewis acid in alcohol facilitates nondestructive solution processing on top of polymer, which boosts hole injection from polymer into metal by two orders of magnitude. By integrating the polymer-acid-metal structure into solar cells, devices exhibit remarkable resilience, retaining 96% ± 3%, 96% ± 2% and 75% ± 7% of their initial efficiencies after continuous operation in nitrogen at 35 °C for 2212 h, 55 °C for 1650 h and 85 °C for 937 h, respectively. Leveraging the Arrhenius relation, we project an impressive T80 lifetime of 26,126 h at 30 °C.
CRIS-Team Scopus Importer:2024-03-15

Practical limits of multijunction solar cells - Peters, Ian Marius; Rodríguez Gallegos, Carlos David; Lüer, Larry; Hauch, Jens; Brabec, Christoph J. (Progress in Photovoltaics, 2023)
Multijunction solar cells offer a path to very high conversion efficiency, exceeding 60% in theory. Under ideal conditions, efficiency increases monotonically with the number of junctions. In this study, we explore technical and economic mechanisms acting on tandem solar cells. We find that these mechanisms produce limitations that are the more pronounced the greater the number of junction is and, hence, limit the ideal number of junctions, as well as the corresponding efficiencies. Spectral variations induce current losses in series-connected tandem solar cells. For Denver, we find that these losses reduce achievable harvesting efficiencies to 51% for non-concentrated light and that they restrict the ideal number of junctions to less than nine. Independently operated solar cells suffer from optical losses with similar consequences. Even high optical efficiencies of 99% restrict the ideal number of junctions to below 10 and reduce achievable efficiencies by more than 10%. Only architectures with a sequential cell illumination are more resilient to these losses. Restricting available materials reveals that a sufficiently low band gap for the bottom cell of 0.9 eV or below is expedient to realize high efficiencies. Economic considerations show that five junctions or less are economically ideal for most conceivable applications.
CRIS-Team Scopus Importer:2023-05-26
Keywords: multijunction solar cell; solar spectrum; techno-economic modelling

Precise control of process parameters for >23% efficiency perovskite solar cells in ambient air using an automated device acceleration platform - Zhang, Jiyun; Wu, Jianchang; Barabash, Anastasia; Du, Tian; Qiu, Shudi; Le Corre, Vincent Marc; Zhao, Yicheng; Zhang, Kaicheng; Schmitt, Frederik; Peng, Zijian; Tian, Jingjing; Li, Chaohui; et al. (Energy and Environmental Science, 2024)
Achieving high-performance perovskite photovoltaics, especially in ambient air, is critically dependent on the precise optimization of process parameters. However, traditional manual methods often struggle to effectively control the key variables. This inherent challenge requires a paradigm shift toward automated platforms capable of precise and reproducible experiments. Herein, we use a fully automated device acceleration platform (DAP) to optimize air-processed parameters for preparing perovskite devices using a two-step sequential deposition technique. Over ten process parameters with significant potential to influence device performance are systematically optimized. Specifically, we delve into the impact of the dripping speed of organic ammonium halide, a parameter that is difficult to control manually, on both perovskite film and device performance. Through the targeted design of experiments, we reveal that the dripping speed significantly affects device performance primarily by adjusting the residual PbI2 content in the films. We find that optimal dripping speeds, such as 50 µL s−1, contribute to top-performance devices. Conversely, excessively fast or slow speeds result in devices with comparatively poorer performance and lower reproducibility. The optimized parameter set enables us to establish a standard operation procedure (SOP) for additive-free perovskite processing in ambient conditions, which yield devices with efficiencies surpassing 23%, satisfactory reproducibility, and state-of-the-art photo-thermal stability. This research underscores the importance of understanding the causality of process parameters in enhancing perovskite photovoltaic performance. Furthermore, our study highlights the pivotal role of automated platforms in discovering innovative workflows and accelerating the development of high-performing perovskite photovoltaic technologies.
CRIS-Team Scopus Importer:2024-07-19

PV module power prediction by deep learning on electroluminescence images - Assessing the physics learned by a convolutional neural network - Lüer, Larry; Forberich, Karen; Hepp, Johannes; Buerhop-Lutz, Claudia; Winkler, Thilo; Rodrigues, Sandy; Hoffmann, Mathis; Doll, Bernd; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Solar Energy Materials and Solar Cells, 2024)
Fast and reliable performance monitoring of photovoltaic modules is essential for economic forecasting in large-scale installations. Deep Learning methods, such as convolutional neural networks, have the potential to predict module power directly from electroluminescence images in an automated workflow. However, neural networks must be trained using large numbers of electroluminescence images of defective modules. Due to budgetary or technical limitations, these training images will always be biased, limiting generalization. Here, we demonstrate a transparent method to discriminate the information learned by a convolutional neural network into generally valid physics and bias. Learning of physics is assessed by providing an artificial, unbiased feature list, which is converted into synthetic electroluminescence images. Using these images, we compare the predictions of the neural network trained on the biased dataset to those of a physics-based equivalent. Bias is assessed by a closer look at the deviations between the predictions from the equivalent circuit model and the trained neural network. The assessment of physics knowledge incorporated by a Deep Learning method gives insight into how the method achieves its predictive capacity.
CRIS-Team Scopus Importer:2023-11-24

Quantifying the Energy Losses in CsPbI2Br Perovskite Solar Cells with an Open-Circuit Voltage of up to 1.45 v - Tian, Jingjing; Zhang, Kaicheng; Xie, Zhiqiang; Peng, Zijian; Zhang, Jiyun; Osvet, Andres; Lüer, Larry; Kirchartz, Thomas; Rau, Uwe; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2022)
CsPbI2Br perovskite solar cells (PSCs) have attracted much interest because of their thermodynamic stability, relatively stable cubic perovskite phase, and their potential as a top cell for tandem applications. However, the open-circuit voltage (VOC) reported to date is in most cases well below the detailed balance (DB) limit for single-junction PSCs. Here, we demonstrate that adding lead acetate to the CsPbI2Br precursor allows us to substantially reduce losses due to nonradiative recombination. Corresponding champion devices reach a power conversion efficiency (-) of 16.7% and a highest VOC value of 1.45 V, which represents 90% of the DB limit for single-junction PSCs at a bandgap of 1.89 eV. In order to disentangle the nonradiative recombination loss mechanisms, we quantify the origin of energy losses by calculating the radiative limit of the open-circuit voltage (VOCrad) and the quasi-Fermi level splitting (QFLS) of perovskite films with and without other functional layers. We further analyze the strategies to reduce the residual losses in order to push the efficiency beyond the 90% theoretical limit.
CRIS-Team Scopus Importer:2022-11-18

Quantitative Analysis of Charge Dissociation by Selectively Characterizing Exciton Splitting Efficiencies in Single Component Materials - He, Yakun; Hanisch, Benedict; Osvet, Andres; Lüer, Larry; Aubele, Anna; Bäuerle, Peter; Li, Weiwei; Li, Ning; Brabec, Christoph (Israel Journal of Chemistry, 2021)
Exciton dissociation between donor and acceptor is the decisive process to determine the photovoltaic performance of organic solar cells (OSCs). The rather fast dynamics of photo-induced charge generation in well-optimized bulk heterojunction (BHJ) composites complicate the quantitative analysis of the charge generation efficiency for donor and acceptor units. Herein, we report time-resolved photoluminescence (TRPL) investigations and demonstrate their potential as a quantitative and contactless characterization technique allowing to separately determine the exciton splitting efficiency of donor and acceptor moieties in selected single component materials. We demonstrate that the exciton splitting efficiency for donor or acceptor moieties can be separately adjusted in these materials by post-treatment, while the corresponding BHJ composites undergo excessive phase separation upon external stress. By relating the separate exciton splitting efficiencies to their photovoltaic performance, the limiting factor in corresponding OSCs, either charge generation or recombination, is identified.
CRIS-Team Scopus Importer:2021-10-22
Keywords: charge dissociation; charge transfer; exciton splitting efficiency; organic solar cells; single component materials; transient photoluminescence

Reducing Open-Circuit Voltage Losses in All-Inorganic Perovskite Cells by Dedoping - Peng, Zijian; Tian, Jingjing; Zhang, Kaicheng; These, Albert; Xie, Zhiqiang; Zhao, Yicheng; Osvet, Andres; Guo, Fei; Lüer, Larry; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2023)
CsPbI2Br is an attractive photovoltaic material due to its promising optoelectronic properties. However, the corresponding perovskite solar cells (PSCs) with p-i-n configuration suffer from low open-circuit voltage (VOC) and fill factor (FF), limiting their application in tandem solar cells. Here, we propose using the fullerene ICBA as the electron charge transporting layer (ETL), forming a better interfacial contact and enhancing the internal quasi-Fermi level splitting (QFLS). A further reduction of VOC losses of around 0.1 V was achieved by an ultrathin phenethylammonium chloride (PEACl) layer between the perovskite and the ETL. We precisely study the VOC improvement and find that passivation of surface recombination contributes only 20 mV, while more importantly, a major increase of 80 mV is achieved by dedoping the perovskite surface, which removes a non-negligible electron extraction barrier. Our results give helpful direction regarding how to further improve VOC in p-i-n perovskite cells.
CRIS-Team Scopus Importer:2023-04-21

Reducing Voltage Losses in Organic Photovoltaics Requires Interfacial Disorder Management - Wang, Rong; Han, Leng; Li, Ning; Chochos, Christos L.; Gregoriou, Vasilis G.; Lüer, Larry; Brabec, Christoph (Advanced Energy Materials, 2024)
Thanks to the introduction of non-fullerene acceptors, efficiencies of organic photovoltaics are now approaching 20%. Closing the gap with inorganic photovoltaics requires minimizing voltage losses without penalizing charge extraction, for which microstructure control is crucial. However, the complex interplay between microstructure and charge generation, recombination, and extraction has so far not been unraveled. Here, a systematic study linking device performance to distinct microstructural features via machine learning is presented. Building bi-layer devices allows to separately study the influence of aggregation and disorder on the energies and lifetimes of bulk and interfacial states. Unambiguous assignments of specific structural motifs to the device photophysics are thus possible. It is found that the control of aggregation-caused quenching is decisive for the exciton splitting efficiency and thus the carrier generation. Furthermore, the static disorder at the donor–acceptor interface controls the nonradiative recombination by shifting the excited state population from the bulk toward the interface. Finally, the amount of disorder in the bulk is found decisive for charge extraction. The finding that charge generation, recombination, and extraction are controlled by distinct structural features, is the key to optimizing these motifs independently, which will pave the way for organic photovoltaics toward the detailed balance limit.
CRIS-Team Scopus Importer:2024-05-03
Keywords: interfacial energy states; machine learning; microstructure; organic solar cells; voltage loss

Revealing Degradation Mechanisms in 3D/2D Perovskite Solar Cells under Photothermal Accelerated Ageing - Peng, Zijian; Vincze, Andrej; Streller, Fabian; Le Corre, Vincent Marc; Zhang, Kaicheng; Li, Chaohui; Tian, Jingjing; Liu, Chao; Luo, Junsheng; Zhao, Yicheng; Späth, Andreas; Fink, Rainer; et al. (Energy and Environmental Science, 2024)
Three-dimensional/two-dimensional (3D/2D) heterojunctions in perovskite solar cells exhibit excellent optoelectronic properties and enhanced stability under mild ageing conditions. However, their performance degrades drastically under harsh ageing conditions. This study reveals the intrinsic instability of mono-ammonium based 2D perovskites (2D-mono) under photo-thermal ageing, which decompose into PbI2 and metallic lead (Pb0). The structural collapse promotes vacancy formation and facilitates iodide migration to the anode. As a result, it triggers a redox reaction that reduces the transport layer’s mobility and doping concentration, leading to a significant increase in series resistance. Compared to mono-ammonium-2D structure, di-ammonium-2D (2D-di) based interfaces demonstrate superior structural stability and effectively block iodide migration into the transporting layer. However, blocking-induced uneven iodide distribution leads to interstitial defect formation in the 3D layer, exacerbating non-radiative recombination. To address it, we propose a strategical method by incorporating 2D-di in the 3D bulk instead of on the top surface, which effectively confines mobile ions within the grain and suppresses cation phase segregation. This optimization yields stable perovskite solar cells with an extrapolated operational T80 lifetime exceeding 560 hours under harsh conditions (85°C and 2-sun illumination

Self-driving AMADAP laboratory: Accelerating the discovery and optimization of emerging perovskite photovoltaics - Zhang, Jiyun; Wu, Jianchang; Stroyuk, Oleksandr; Raievska, Oleksandra; Lüer, Larry; Hauch, Jens; Brabec, Christoph (Mrs Bulletin, 2024)
The development of new solar materials for emerging perovskite photovoltaics poses intricate multi-objective optimization challenges in a large high-dimensional composition and parameter space, with in some cases, millions of potential candidates to be explored. Solving it necessitates reproducible, user-independent laboratory work and intelligent preselection of innovative experimental methods. Materials Acceleration Platforms (MAPs) seamlessly combine robotic materials synthesis, characterization, and AI-driven data analysis, enabling the exploration of new materials. They revolutionize material development by replacing trial-and-error methods with precise, rapid experimentation and generating high-quality data for training machine learning (ML) algorithms. Device Acceleration Platforms (DAPs) focus on optimizing functional energy films and multilayer stacks. Unlike MAPs, DAPs concentrate on refining processing conditions for predetermined materials, crucial for disordered semiconductors. By fine-tuning processing parameters, DAPs significantly advance disordered semiconductor devices such as emerging photovoltaics. This article examines recent advancements in automated laboratories for perovskite material discovery and photovoltaics device optimization, showcasing in-house-developed MAPs and a DAP. These platforms cover the entire value chain, from materials to devices, addressing optimization challenges through robot-based high-throughput experimentation (HTE). Ultimately, a self-driven Autonomous Material and Device Acceleration Platforms (AMADAP) laboratory concept is proposed for autonomous functional solar material discovery using AI-guided combinational approaches.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Autonomous research; Chemical synthesis; Machine learning; Perovskites; Photovoltaic; Semiconducting

Simulation of perovskite thin layer crystallization with varying evaporation rates - Majewski, M.; Qiu, Shudi; Ronsin, O.; Lüer, Larry; Le Corre, Vincent Marc; Du, Tian; Brabec, Christoph; Egelhaaf, Hans-Joachim; Harting, J. (Materials Horizons, 2024)
Perovskite solar cells (PSC) are promising potential competitors to established photovoltaic technologies due to their superior efficiency and low-cost solution processability. However, the limited understanding of the crystallization behaviour hinders the technological transition from lab-scale cells to modules. In this work, advanced phase field (PF) simulations of solution-based film formation are used for the first time to obtain mechanistic and morphological information that is experimentally challenging to access. The well-known transition from a film with many pinholes, for a low evaporation rate, to a smooth film, for high evaporation rates, is recovered in simulation and experiment. The simulation results provide us with an unprecedented understanding of the crystallization process. They show that supersaturation and crystallization confinement effects determine the final morphology. The ratio of evaporation to crystallization rates turns out to be the key parameter driving the final morphology. Increasing this ratio is a robust design rule for obtaining high-quality films, which we expect to be valid independently of the material type.
CRIS-Team Scopus Importer:2024-11-22

Single-Walled Carbon Nanotubes as an Additive in Organic Photovoltaics: Effects on Carrier Generation and Recombination Dynamics - Abudulimu, Abasi; Eckstein, Klaus; El Gemayel, Mirella; Namal, Imge; Phillips, Adam B.; Ellingson, Randy J.; Heben, Michael J.; Hertel, Tobias; Meier, Sebastian B.; Lüer, Larry (Solar RRL, 2022)
Employing single-walled carbon nanotubes (SWNTs) as an additive in the active layer of organic photovoltaics (OPV) to improve charge extraction is gaining weight in the research community. While SWNTs can transport charge carriers orders of magnitudes faster than conventional polymers, they also quench excitons and trap-free charges, reducing device performance. Such influences of SWNTs on OPV device performance remain inadequately explored and incompletely understood. Herein, the impact of SWNTs, enriched in (6,5) chirality, on the charge generation and extraction properties of two different OPV devices is studied by femtosecond-microsecond transient absorption spectroscopy and transient photovoltage/photocurrent techniques. It is shown that depending on the donor material properties (e.g., energetics), SWNTs can reduce carrier generation by quenching the excitons and increase carrier recombination through trapping processes. Then, by performing an analytical calculation of the currentvoltage characteristics of the devices using the parameters determined via the transient measurements, it is shown that the increased recombination also relates to morphological changes induced by the SWNTs. These results shed light on the performance limiting factors of the SWNTs when incorporated into the active layer of the solar cells. This work thus can accelerate the blend optimization process for high-performance organic solar cells.
CRIS-Team WoS Importer:2022-02-11

Suppressing Nonradiative Recombination in Lead-Tin Perovskite Solar Cells through Bulk and Surface Passivation to Reduce Open Circuit Voltage Losses - Zhang, Kaicheng; Späth, Andreas; Almora, Osbel; Le Corre, Vincent Marc; Wortmann, Jonas; Zhang, Jiyun; Xie, Zhiqiang; Barabash, Anastasia; Hammer, Maria; Heumüller, Thomas; Min, Jie; Fink, Rainer; et al. (ACS Energy Letters, 2022)
Lead-Tin perovskite solar cells (Pb/Sn PSCs) are limited by the intrinsic instability of Sn(II), which tends to oxidize forming Sn vacancies in perovskite films. Herein, a Lewis base β-guanidinopropionic acid (GUA) and hydrazinium iodide (HAI) are introduced to effectively passivate the perovskite bulk and surface, respectively. The synergistic approach leads to Pb/Sn PSCs with a promising power conversion efficiency of 20.5% owing to the significantly reduced nonradiative recombination and voltage losses. As a result, the VOC × FF product of PSCs is significantly improved, which is among the highest values documented in the literature, being favorable for perovskite-based tandem applications. Additionally, the strategy demonstrated in this work could also improve the stability of PSCs by enhancing the chemical robustness of the perovskite layer. These results emphasize the significance of bulk and surface passivation in the development of efficient and stable PSCs based on Pb/Sn perovskites.
CRIS-Team Scopus Importer:2022-09-30

Tailoring the Dimensionality of 2D/3D Heterojunctions for Inverted Perovskite Solar Cells - Li, Chaohui; Zhang, Kaicheng; Maiti, Santanu; Peng, Zijian; Tian, Jingjing; Park, Hyoungwon; Byun, Jiwon; Xie, Zhiqiang; Dong, Lirong; Qiu, Shudi; Bornschlegl, Andreas; Liu, Chao; et al. (ACS Energy Letters, 2024)
Interface engineering is crucial to achieving stable perovskite photovoltaic devices. A versatile approach is developed to tailor interface properties via integrating co-assembled monolayers (co-SAMs) at the p-type buried interface and by capping a two-dimensional (2D) perovskite layer at the n-type upper interface with vacuum quenching. Optimized co-SAMs promote the coverage of the hole transport layer, significantly reducing the incidence of leakage currents. Based on this foundation, we develop damp-heat-stable perovskite solar cells by precisely tailoring the fragments of 2D perovskite layers through vacuum annealing with phenethylammonium iodide. An impressive open-circuit voltage of 1.216 V is achieved, corresponding to 92% of the value determined by the detailed-balance limit, along with a power conversion efficiency of 23.68%. Ultimately, integrating co-SAMs and the vacuum-assisted annealing fabricated devices maintain 96% and 80% of initial efficiencies after 1200 and 500 h of tracking at a maximum power point under 55 and 85 °C, respectively.
CRIS-Team Scopus Importer:2024-02-23

Tailoring the Nature of Interface States in Efficient and Stable Bilayer Organic Solar Cells by a Transfer-Printing Technique - Wang, Rong; Jiang, Youyu; Gruber, Wolfgang; He, Yakun; Wu, Mingjian; Weitz, Paul; Zhang, Kaicheng; Lüer, Larry; Forberich, Karen; Unruh, Tobias; Spiecker, Erdmann; Deibel, Carsten; et al. (Advanced Materials Interfaces, 2022)
Bulk heterojunction organic solar cells (BHJ-OSCs) are designed to overcome inefficient charge generation and limited exciton diffusion of organic semiconductors. However, there are some disadvantages involving inherent voltage losses, microstructure control, and operational instability. Bilayer solar cells (BL-OSCs) without mixed regions are free from these problems and offer a platform to explore the photophysical processes at the donor-acceptor interface. Here, a breakthrough for n-i-p BL-OSCs in charge generation efficiency is reported. A gradual adjustment of the molecular interface orientation of the polymer donor (PM6) is accompanied by the evolution of charge-transfer states and Forster energy transfer. Besides, less recombination losses and superior morphological stability of BL-OSCs are achieved at a PCE comparable to that of BHJ-OSCs with similar layer thickness. This investigation confirms the feasibility of manufacturing BL-OSCs by a transfer printing method and provides a versatile architecture to study fundamental interface phenomena in OSCs independent from microstructure disorder.
CRIS-Team WoS Importer:2022-04-29

The role of exciton lifetime for charge generation in organic solar cells at negligible energy-level offsets - Classen, Andrej; Chochos, Christos L.; Lüer, Larry; Gregoriou, Vasilis G.; Wortmann, Jonas; Osvet, Andres; Forberich, Karen; McCulloch, Iain; Heumüller, Thomas; Brabec, Christoph (Nature Energy, 2020)
Organic solar cells utilize an energy-level offset to generate free charge carriers. Although a very small energy-level offset increases the open-circuit voltage, it remains unclear how exactly charge generation is affected. Here we investigate organic solar cell blends with highest occupied molecular orbital energy-level offsets (∆EHOMO) between the donor and acceptor that range from 0 to 300 meV. We demonstrate that exciton quenching at a negligible ∆EHOMO takes place on timescales that approach the exciton lifetime of the pristine materials, which drastically limits the external quantum efficiency. We quantitatively describe this finding via the Boltzmann stationary-state equilibrium between charge-transfer states and excitons and further reveal a long exciton lifetime to be decisive in maintaining an efficient charge generation at a negligible ∆EHOMO. Moreover, the Boltzmann equilibrium quantitatively describes the major reduction in non-radiative voltage losses at a very small ∆EHOMO. Ultimately, highly luminescent near-infrared emitters with very long exciton lifetimes are suggested to enable highly efficient organic solar cells.
CRIS-Team Scopus Importer:2020-09-11

Understanding Causalities in Organic Photovoltaics Device Degradation in a Machine-Learning-Driven High-Throughput Platform - Liu, Chao; Lüer, Larry; Le Corre, Vincent Marc; Forberich, Karen; Weitz, Paul; Heumüller, Thomas; Du, Xiaoyan; Wortmann, Jonas; Zhang, Jiyun; Wagner, Jerrit; Ying, Lei; Hauch, Jens; et al. (Advanced Materials, 2023)
Organic solar cells (OSCs) now approach power conversion efficiencies of 20%. However, in order to enter mass markets, problems in upscaling and operational lifetime have to be solved, both concerning the connection between processing conditions and active layer morphology. Morphological studies supporting the development of structure–process–property relations are time-consuming, complex, and expensive to undergo and for which statistics, needed to assess significance, are difficult to be collected. This work demonstrates that causal relationships between processing conditions, morphology, and stability can be obtained in a high-throughput method by combining low-cost automated experiments with data-driven analysis methods. An automatic spectral modeling feeds parametrized absorption data into a feature selection technique that is combined with Gaussian process regression to quantify deterministic relationships linking morphological features and processing conditions with device functionality. The effect of the active layer thickness and the morphological order is further modeled by drift–diffusion simulations and returns valuable insight into the underlying mechanisms for improving device stability by tuning the microstructure morphology with versatile approaches. Predicting microstructural features as a function of processing parameters is decisive know-how for the large-scale production of OSCs.
CRIS-Team Scopus Importer:2023-04-28
Keywords: device stability; Gaussian process regression (GPR) prediction; linear Pearson correlations; machine learning; organic solar cells

Understanding the Limitations of Charge Transporting Layers in Mixed Lead–Tin Halide Perovskite Solar Cells - Zhang, Kaicheng; Forberich, Karen; Lüer, Larry; García Cerrillo, José; Meng, Wei; Du, Xiaoyan; Le Corre, Vincent Marc; Zhao, Yicheng; Niu, Tianqi; Xue, Qifan; Koster, L Jan Anton; Li, Ning; et al. (Advanced Energy and Sustainability Research, 2021)

Understanding the Microstructure Formation of Polymer Films by Spontaneous Solution Spreading Coating with a High-Throughput Engineering Platform - Wang, Rong; Lüer, Larry; Langner, Stefan; Heumüller, Thomas; Forberich, Karen; Zhang, Heyi; Hauch, Jens; Li, Ning; Brabec, Christoph (Chemsuschem, 2021)
An important step of the great achievement of organic solar cells in power conversion efficiency is the development of low-band gap polymer donors, PBDB−T derivatives, which present interesting aggregation effects dominating the device performance. The aggregation of polymers can be manipulated by a series of variables from a materials design and processing conditions perspective; however, optimization of film quality is a time- and energy-consuming work. Here, we introduce a robot-based high-throughput platform (HTP) that is offering automated film preparation and optical spectroscopy thin-film characterization in combination with an analysis algorithm. PM6 films are prepared by the so-called spontaneous film spreading (SFS) process, where a polymer solution is coated on a water surface. Automated acquisition of UV/Vis and photoluminescence (PL) spectra and automated extraction of morphological features is coupled to Gaussian Process Regression to exploit available experimental evidence for morphology optimization but also for hypothesis formulation and testing with respect to the underlying physical principles. The integrated spectral modeling workflow yields quantitative microstructure information by distinguishing amorphous from ordered phases and assesses the extension of amorphous versus the ordered domains. This research provides an easy to use methodology to analyze the exciton coherence length in conjugated semiconductors and will allow to optimize exciton splitting in thin film organic semiconductor layers as a function of processing.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Gaussian process regression; high-throughput engineering; microstructure morphology; organic photovoltaics; spontaneous film spreading

Unraveling the Charge-Carrier Dynamics from the Femtosecond to the Microsecond Time Scale in Double-Cable Polymer-Based Single-Component Organic Solar Cells - He, Yakun; Wang, Bingzhe; Lüer, Larry; Feng, Guitao; Osvet, Andres; Heumüller, Thomas; Liu, Chao; Li, Weiwei; Guldi, Dirk Michael; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2021)
Single-component organic solar cells (SCOSCs) have witnessed great improvement during the last few years with the champion efficiency jumping from the previous 2-3% to currently 6-11% for the representative material classes. However, the photophysics in many of these materials has not been sufficiently investigated, lacking essential information regarding charge-carrier dynamics as a function of microstructure, which is highly demanded for a better understanding and potential guidance for further improvements. In this work, for the first time, the charge-carrier dynamics of a representative double-cable polymer, which achieves efficiencies of over 6% as an active layer in SCOSCs, is investigated across seven orders of magnitude in time scale, from fs-ps charge generation to ns-mu s charge recombination processes. Specific emphasis is placed on understanding the impact of thermal post-treatment on the charge dissociation and recombination dynamics. Annealing the photoactive layer at 230 degrees C results in the highest photovoltaic performance because of efficient charge generation in parallel to suppressed recombination. This work intends to present a complete picture of the charge-carrier dynamics in SCOSCs using the representative double-cable polymer PBDBPBI-Cl.
CRIS-Team WoS Importer:2021-12-31

Unraveling the Role of Non-Fullerene Acceptor with High Dielectric Constant in Organic Solar Cells - Zhang, Yue; He, Yakun; Zeng, Liang; Lüer, Larry; Deng, Wanyuan; Chen, Yuting; Zhou, Jiadong; Wang, Zhiqiang; Brabec, Christoph; Wu, Hongbin; Xie, Zengqi; Duan, Chunhui (Small, 2023)
Increasing the relative dielectric constant is a constant pursuit of organic semiconductors, but it often leads to multiple changes in device characteristics, hindering the establishment of a reliable relationship between dielectric constant and photovoltaic performance. Herein, a new non-fullerene acceptor named BTP-OE is reported by replacing the branched alkyl chains on Y6-BO with branched oligoethylene oxide chains. This replacement successfully increases the relative dielectric constant from 3.28 to 4.62. To surprise, BTP-OE offers consistently lower device performance relative to Y6-BO in organic solar cells (16.27% vs 17.44%) due to the losses in open-circuit voltage and fill factor. Further investigations unravel that BTP-OE has resulted in reduced electron mobility, increased trap density, enhanced first order recombination, and enlarged energetic disorder. These results demonstrate the complex relationship between dielectric constant and device performance, which provide valuable implications for the development of organic semiconductors with high dielectric constant for photovoltaic application.
CRIS-Team Scopus Importer:2023-05-26
Keywords: dielectric constant; energetic disorder; first order recombination; non-fullerene acceptors; organic solar cells

Unravelling material properties of halide perovskites by combined microwave photoconductivity and time-resolved photoluminescence spectroscopy - Kupfer, Christian; Le Corre, Vincent Marc; Li, Chaohui; Lüer, Larry; Forberich, Karen; Kato, Masashi; Osvet, Andres; Brabec, Christoph (Journal of Materials Chemistry C, 2024)
To take advantage of the huge compositional space of metal halide perovskites, a reliable and fast characterization method is required. By combining time-resolved photoluminescence (trPL) with microwave photoconductivity measurements, we are able to rapidly extract fundamental material properties of promising perovskite materials from bare films. This is achieved by incorporating a rate-equation model into a fitting algorithm based on Bayesian optimization to globally fit the experimental results. Including microwave photoconductivity measurements into our analysis significantly enhances the accuracy of estimating recombination rate constants. Additionally, it grants us the ability to determine the ratio of electron and hole mobilities, a crucial charge transport property that cannot be obtained solely through time-resolved photoluminescence measurements. Furthermore, the high sensitivity of microwave photoconductivity measurements to long-lived trap states yields information about the trap-assisted recombination, which is a major source of efficiency loss for solar devices and is difficult to assess from pure trPL measurements. In this work, we introduce the fundamental principles of microwave photoconductivity, along with the employed rate-equation model and fitting techniques. We then outline the procedure for conducting measurements and extracting the recombination rate constants, trap density, and mobility ratio. Subsequently, we highlight the benefits of combining both methods through a comparison of results from fits using only trPL with those from fits incorporating combined signals on a simulated dataset. We also discuss the merits of conducting intensity-dependent measurements. Finally, we present the annealing-dependent results obtained from a highly relevant triple-cation, mixed-halide perovskite, FA0.82MA0.13Cs0.05Pb(I0.87Br0.13)3, as an application example, where we uncover the presence of long-lived traps beyond 10 μs.
Created from Fastlane, Scopus look-up

Unveiling the Role of BODIPY Dyes as Small-Molecule Hole Transport Material in Inverted Planar Perovskite Solar Cells - Seoneray, Isabel; Wu, Jianchang; Rocha-Ortiz, Juan S.; Bornschlegl, Andreas; Barabash, Anastasia; Wang, Yunuo; Lüer, Larry; Hauch, Jens; García, Angélica; Zapata-Rivera, Jhon; Brabec, Christoph J.; Ortiz, Alejandro (Solar RRL, 2024)
Perovskite solar cells (PSCs) have become a research hotspot since their dramatic increase in power conversion efficiency (PCE), surpassing 26% due to advances in cell engineering and interfacial layers. Within the last factor, hole transporting materials play a crucial role in enhancing device performance and stability. Among several molecular building blocks, BODIPYs are attractive for the design of novel hole transporting material (HTMs) due to their outstanding photophysical and charge transport properties easily tuned by synthetic modifications. Herein, the synthesis of five new BODIPY-based HTMs PyBDP 1–5 are reported, functionalized at the meso- and α- positions with pyrenyl and arylamino units, respectively. The resulting compounds exhibit broad absorption in the visible region, remarkable thermal stability, narrow bandgaps, suitable energy levels, and good hole extraction capability, as subtracted from experimental and computational characterizations. The performance of the BODIPY derivatives as HTMs is evaluated in planar inverted (p-i-n) PSCs and compared to commonly used PTAA, resulting in highly efficient systems, reaching PCEs very close to that obtained with the reference polymer (21.51%). The incorporation of these BODIPY-based HTMs result in an outstanding PCE of 20.37% for devices including PyBDP-1 and 19.97% for devises containing PyBDP-3, thus demonstrating that BODIPY derivatives are a promising alternative to obtain simple and efficient organic HTMs.
CRIS-Team Scopus Importer:2024-05-31
Keywords: arylamine; BODIPY; hole-transporting material; perovskite solar cells; pyrene